2004
DOI: 10.1007/s00221-003-1799-4
|View full text |Cite
|
Sign up to set email alerts
|

When practice leads to co-articulation: the evolution of geometrically defined movement primitives

Abstract: The skilled generation of motor sequences involves the appropriate choice, ordering and timing of a sequence of simple, stereotyped movement elements. Nevertheless, a given movement element within a well-rehearsed sequence can be modified through interaction with its neighboring elements (co-articulation). We show that extensive training on a sequence of planar hand trajectories passing through several targets resulted in the co-articulation of movement components, and in the formation of new movement elements… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
182
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(193 citation statements)
references
References 39 publications
9
182
2
Order By: Relevance
“…This learning may and may not be effector-specific . Effector-specific sequence learning is indicated by performance reduction when another effector (finger or hand) is used than during practice, and that has been observed in many different motor tasks (Doya, 2000;MacNeilage, 1970;Mattys, 2004;Park & Shea, 2003;Shea & Wulf, 2005;Sosnik, Hauptmann, Karni, & Flash, 2004), including the serial RT task (Deroost, Zeeuws, & Soetens, 2005;Keele et al, 1995;Verwey & Clegg, 2005). In the serial RT task, effector-specific learning has even been demonstrated by the capacity to learn a sequence with the fingers of one hand while the other hand performs a random sequence (Berner & Hoffmann, 2009).…”
Section: External Sequence Control: Speeding Up Reactionsmentioning
confidence: 99%
“…This learning may and may not be effector-specific . Effector-specific sequence learning is indicated by performance reduction when another effector (finger or hand) is used than during practice, and that has been observed in many different motor tasks (Doya, 2000;MacNeilage, 1970;Mattys, 2004;Park & Shea, 2003;Shea & Wulf, 2005;Sosnik, Hauptmann, Karni, & Flash, 2004), including the serial RT task (Deroost, Zeeuws, & Soetens, 2005;Keele et al, 1995;Verwey & Clegg, 2005). In the serial RT task, effector-specific learning has even been demonstrated by the capacity to learn a sequence with the fingers of one hand while the other hand performs a random sequence (Berner & Hoffmann, 2009).…”
Section: External Sequence Control: Speeding Up Reactionsmentioning
confidence: 99%
“…It has been shown that geometrically defined movement features can be acquired by the human motor system (Sosnik et al, 2004), before the specification of kinematic attributes such as movement speed Zipser, 2002, 2004). It is thus conceivable that separate planning constraints may be imposed at the geometric and temporal levels.…”
Section: Introductionmentioning
confidence: 99%
“…More specifically, based on several studies relating the neural basis of modularity to the development of skilled movements (15)(16)(17), we expected that functional brain networks derived from acquisition of a simple motor skill would display modular structure over the variety of temporal scales associated with learning (18). We also hypothesized that modular structure would change dynamically during learning (4,19), and that characteristics of such dynamics would be associated with learning success.…”
mentioning
confidence: 99%